Contextual fear conditioning in humans using feature-identical contexts - Bäuchl, Christian; Flor, Herta (Neurobiology of learning and memory, 2015)
Contextual fear conditioning studies in animals and humans found an involvement of the hippocampus and amygdala during fear learning. To exclude a focus on elements of the context we employed a paradigm, which uses two feature-identical contexts that only differ in the arrangement of the features and requires configural processing. We employed functional magnetic resonance imaging to determine the role of the hippocampus and neocortical areas during the acquisition of contextual fear in humans. For contextual fear acquisition, we paired one context (CS+) with an aversive electrical stimulus, whereas the other (CS−) was never followed by aversive stimulation. Blood oxygen level dependent activation to the CS+ was present in the insula, inferior frontal gyrus, inferior parietal lobule, superior medial gyrus and caudate nucleus. Furthermore, the amygdala and hippocampus were involved in a time-dependent manner. Psychophysiological interaction analyses revealed functional connectivity of a more posterior hippocampal seed region with the anterior hippocampus, posterior cingulate cortex and superior parietal lobule. The anterior hippocampus was functionally coupled with the amygdala and postcentral gyrus. This study complements previous findings in contextual fear conditioning in humans and provides a paradigm which might be useful for studying patients with hippocampal impairment.